A block-based selection method for road network generalization - Gulgen, F.; Gokgoz, T. (TAYLOR & FRANCIS LTD, 2011)
When road symbols are shown in a size proportionate to the reduced scale, several problems of legibility may arise concerning the urban blocks. By the method proposed in this paper, in order to overcome these problems, urban block areas are enlarged through amalgamation and the intervening roads in the amalgams are eliminated. This method includes two new approaches for computation of threshold used in determination of important roads based on the connectivity measure, and for definition of minimum block space and area requirements based on graphic limits. A block life cycle was designed for amalgamation of blocks. For the amalgamation process, a new algorithm was developed. The experimental testing indicates that important roads and the roads surrounding the urban area have been preserved. A simpler and more legible road network has been acquired. This method can be described as a more holistic approach as the buildings are taken into account. The problems arising in the experimental testing indicate that the cartographic selection/elimination process is not sufficient by itself for road network generalization, which can be assumed as one of the integral parts of Digital Earth. As well as the selection/elimination, processes such as displacement and caricaturizing are also needed.
Keywords: GIS; cartographic generalization; selection/elimination; road network; Digital Earth; Physical Geography; Remote Sensing